0.5(x+6)+1.5(x-5)=

Simple and best practice solution for 0.5(x+6)+1.5(x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5(x+6)+1.5(x-5)= equation:


Simplifying
0.5(x + 6) + 1.5(x + -5) = 0

Reorder the terms:
0.5(6 + x) + 1.5(x + -5) = 0
(6 * 0.5 + x * 0.5) + 1.5(x + -5) = 0
(3 + 0.5x) + 1.5(x + -5) = 0

Reorder the terms:
3 + 0.5x + 1.5(-5 + x) = 0
3 + 0.5x + (-5 * 1.5 + x * 1.5) = 0
3 + 0.5x + (-7.5 + 1.5x) = 0

Reorder the terms:
3 + -7.5 + 0.5x + 1.5x = 0

Combine like terms: 3 + -7.5 = -4.5
-4.5 + 0.5x + 1.5x = 0

Combine like terms: 0.5x + 1.5x = 2x
-4.5 + 2x = 0

Solving
-4.5 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4.5' to each side of the equation.
-4.5 + 4.5 + 2x = 0 + 4.5

Combine like terms: -4.5 + 4.5 = 0.0
0.0 + 2x = 0 + 4.5
2x = 0 + 4.5

Combine like terms: 0 + 4.5 = 4.5
2x = 4.5

Divide each side by '2'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| z^2-20=0 | | 3(1+h)=3h-9 | | 7y^2+12y=0 | | .8x=43 | | 3s^3-16s+5= | | 2x^2+4x+5=x | | -6y^2+53y+9= | | -.22x=.4 | | 32.31+31.32x=41.89 | | 2log^3x=log^3(x+6) | | 1.25x=3.75 | | 2xsquared+8=0 | | -10x^2+79x+8= | | 4x^2-28x+13=0 | | k*3(x-12)-3x=12 | | -7(m)=-42 | | P=a+b+4csolving | | p(5)=10-2q | | 6x=-2x-4.5 | | p-6=-9 | | x+.105x=35.7 | | 2y-8x=13 | | 3c=451.89-358.92 | | y^2+9y+162=0 | | c=3(451.89-358.92) | | 358.92+c+c+c=451.89 | | 3500000+168000x=300440 | | (x-2i)(x-2i)=0 | | 358.92+3c=451.89 | | 3(2x-5)=x+15 | | 5[2x+3]=15 | | 451.89-3c=358.92 |

Equations solver categories